Is the hybrid method more adequate for measuring operational risk? - Farsiah, Lena; Amalia, Euis; Saharuddin, Desmadi; Lukman, Lukman (Journal of Accounting and Investment, 2024)
Research aims: Risk management in financial institutions struggles with setting suitable capital charges for operational losses, resulting in large, disproportionate reserves that impact profits. This study, therefore, aims to develop a tailored operational risk measurement model for general takaful companies, addressing this challenge and optimizing capital allocation.Design/Methodology/Approach: This study employed a hybrid approach, merging the loss distribution approach (LDA) with historical data and scenario analysis for insurance company loss events. Compiling data into distributions, it utilized Monte Carlo simulations to determine value at risk (VaR). The resulting VaR guided the calculation of operational risk capital charges for future periods.Research findings: Measurement using the hybrid method could produce more adequate operational risk capital charges. These results confirm the acceptability of the VaR calculation and have been validated by the Kupic test.Theoretical contribution/Originality: This research offers a more comprehensive alternative method of measuring operational risk by combining historical company data with expert opinions, making it more likely to be practiced in the industry.Practitioner/Policy implication: The results of this study put forward an alternative, more suitable model for industry and regulators to measure operational risk management in general takaful companies.